Bank’s risk-taking channel of monetary policy and TLTRO : evidence from the Eurozone - Afonso, António (2024)
Using a panel data approach with bank-fixed effects, we study the impact of Targeted Longer-Term Refinancing Operations (TLTRO) on banks’ risk, given by their distance to default (DtD). The study aims to determine if the liquidity from TLTROs influences banks' risk-taking behaviour. For the period from 2012:Q1 to 2018:Q4, covering 90 listed banks from 16 Eurozone countries, our findings show that TLTRO is associated with an increase in banks' default risk. However, banks that participated in TLTRO experienced a positive effect on their default risk, indicating that they may have used liquidity to strengthen their financial position. Furthermore, we found no evidence that TLTRO liquidity encouraged banks to significantly increase lending or invest in riskier assets. Finally, our results also suggest that TLTRO’s impact is consistent across banks of different sizes and that the competition within the banking sector does not influence how banks utilize TLTRO liquidity.